A Review of the Actions of Endogenous and Exogenous Vasoactive Substances During the Estrous Cycle and Pregnancy in Rats - Martinez-Salinas, J; Morales-Munoz, B; Jaimes-Fernandez, L (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Vascular endothelium plays a key role in regulating cardiovascular homeostasis by controlling the vascular tone. Variations in sex hormones during the reproductive cycle of females affect the homeostasis of the cardiovascular system. Also, the evidence shows that estrogens show a cardioprotective effect. On this basis, this study describes some vascular responses induced by vasoactive substances during the estrous cycle in rats. We obtained the information available on this topic from the online databases that included scientific articles published in the Web of Science, PubMed, and Scielo. Many investigations have evaluated the vasoactive response of substances such as acetylcholine and norepinephrine during the estrous cycle. In this review, we specifically described the vascular response to vasoactive substances in rats during the estrous cycle, pregnancy, and in ovariectomized rats. In addition, we discussed the existence of different signaling pathways that modulate vascular function. The knowledge of these effects is relevant for the optimization and development of new treatments for some vascular pathologies. © 2019 by the authors.